Traditional Retailer’s Intention to opt E-commerce for Digital Retail Business in Saudi Arabia - Alateeg, Sultan Saleh; Alhammadi, Abdulaziz Dakhel (Migration Letters, 2023)
This study investigates the factor affecting traditional retailer’s intention to opt e-commerce in the context of digital retail business in Saudi Arabia. Employing a cross-sectional survey methodology, structured questionnaires were administered to traditional retailers, providing a snapshot of their perceptions and intentions regarding e-commerce adoption. The data analysis was conducted utilizing the PLS-based structural equation modeling method. The study reveals that perceived usefulness is a pivotal driver, positively impacting the intention to opt e-commerce. Moreover, attitude towards e-commerce is significantly influenced by perceived usefulness and ease of use, highlighting the importance of user-friendly platforms. Conversely, high perceived costs can deter a positive attitude. Overcoming technological barriers is also instrumental, as they can foster a more favorable attitude. Intriguingly, organizational and environmental barriers had limited direct impact on attitude, indicating that internal and individual factors play a more substantial role in shaping the attitudes of traditional retailers in Saudi Arabia. The insights garnered from this research hold substantial significance for the traditional retail industry, government authorities, and all relevant stakeholders invested in facilitating the successful incorporation of e-commerce into Saudi Arabia’s established retail sector. This integration is pivotal in ensuring a competitive edge within the dynamic landscape of digital retail. Understanding these factors is vital as the retail landscape continues to evolve, bridging the gap between traditional and digital retail models.